On the role of imagery modalities on motor learning - Toussaint, L.; Blandin, Y. (Journal of Sports Sciences, 2010)
In the present study, we examine specifically how the sensory conditions available during physical practice of a task might influence the subsequent use of motor imagery. First, as a pre-test, participants had to physically reproduce knee joint positions with or without vision. Second, they practised motor imagery (15 and 150 trials) with visual, kinaesthetic or visuo-kinaesthetic imagery. A control group with no imagery was included. Post-tests were then performed 10 min and 24 h after each imagery session in a sensory condition similar to that used in the pre-test. Results showed that efficient motor imagery instructions have to take account of the sensory information available during physical experience of the task: kinaesthetic or visuo-kinaesthetic imagery in a no-vision condition, and visual imagery or, to a lesser extent, visuo-kinaesthetic imagery in a vision condition. Discussion focuses on the role of sensory motor memory on motor prediction to simulate a specific movement, and on the similarities between physical and mental practice in the development of sensory-specific movement representation.